Ajustes na rigidez dinâmica das articulações do membro inferior em resposta a diferentes condições de marcha - Thiago Ribeiro Teles dos Santos (2016)
The studies presented in this thesis aimed to investigate how occur adjustments to the dynamic stiffness of the joints of the lower limb in situations that require an increased demand on the musculoskeletal system. The first study investigated these adjustments across the load increase transported to the floor. Specifically, it analyzed the dynamic stiffness of the lower limb joints and the orientation of the total mass center of the system (participant and backpack - CMtsis) with respect to the ankle and the knee. Thirteen subjects were assessed in both gear conditions: without load and under load (load corresponding to 30% of body weight). The dynamic stiffness was calculated as the slope of the time curve joint x joint angle during key stages of power absorption ankle joint, knee and hip in the sagittal plane. Were calculated two angles in the sagittal plane (1) between a vertical and a vector connecting the location of CMtsis the ankle (CMtsis-ankle) and (2) between a vertical and a vector connecting the location of CMtsis the knee (CMtsis -knee). These angles were analyzed during power absorption stages ankle joint and knee, as well as removed from the ground up. the dynamic rigidity of the hip not changed at the start of power absorption phase and the joint removal of the foot. the second study investigated the stiffness adjustments DYNAMICS due to increased running speed. Thirty-five subjects were assessed in two randomized conditions: autosselecionada speed and speed 25% higher than autoselecionada. the dynamic stiffness and the angle between the vertical and the vector of the body center of mass (CM) to the ankle (CM-ankle) and knee (CM-knee) in the sagittal plane were calculated similarly to the first study. Different time curve patterns articulate x joint angle of the ankle were observed and the subjects were categorized according to the standard adopted in the conditions. sex deo participant was considered during the analysis. the change of the dynamic stiffness of the ankle with increasing speed was dependent on the adopted standard. The standard with most mechanical energy harnessing potential in ankle increased by dynamic stiffness in that joint. The knee had the highest increase in stiffness between articulaões . There was an increase in the dynamics of hip stiffness. the participant's sex only influenced the dynamics of ankle stiffness, where men had higher values than women. The CM- CM ankle and knee angles auemntaram with increasing speed in most analyzer. The findings of both studies indicate that the joints of the lower limb changed the dynamic stiffness differently. Understanding these adjustments in the dynamic stiffness can contribute to the understanding of gait disorders and the development of locomotion aid implements.